Comparative analysis of academic performance of extended and mainstream programme students in the sociology discipline of a South African University - Moruri - Silo, Puleng A; Obioha, Emeka E. (Social Sciences, Humanities and Education Journal (SHE Journal), 2024)
This study aims at examining the academic performance of students in the Extended programme (4-year qualification) as compared to the Mainstream programme (3-year programme) in the Sociology Unit at the Walter Sisulu University. It aims to establish whether there is a significant difference between extended programme students and those registered in the mainstream programme. This study sought to investigate whether the Mainstream programme performs better than Extended Curricula Program students as expected by the South African Council of Higher Education and the Department of Higher Education and Training and this was done over a period of three years (2019, 2020, and 2021). Findings in the study indicate a positive percentage improvement for mainstream in 2020 and negative percentage changes for many extended curricula modules in 2021. This shows that extended curricula may develop or perform better than mainstream curricula over a three-year period. However, there are negative changes that indicate declines or poor performance in expanded curricula when compared to mainstream curricula. Overall, while the mainstream students outperform the extended curriculum ones in some modules and years, the extended curriculum students also paced over the mainstream in other instances. Mainstream. While it is established that the mainstream students are slightly ahead, the extended curriculum students are not comparatively worse off. Attention should rather be paid to module specificity to improve the performance of the extended programme students, where they lagged the mainstream.